Urgensi Pelaksanaan Supervisi Akademik dalam Peningkatan Kompetensi Guru di Era Merdeka Belajar - Rahma, Zaqia; Triwiyanto, Teguh (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Indonesia is ranked 74 out of 79 countries in terms of reading, science, and math skills. One of the factors for the low quality of education in Indonesia is the lack of teacher competence in preparing learning media and methods. In this 21st era, Indonesia has implemented an independent learning policy that frees teachers and students from choosing learning methods. One of the efforts that can be made to improve teacher competence is the implementation of academic supervision. The purpose of this study was to determine the importance of implementing academic supervision and the role of school principals in implementing academic supervision. The research was conducted using a meta-analysis that collected data and information from several studies. The findings of this study found that academic supervision activities are an effective tool for solving teacher problems and as a means of improving teacher competence. The role of the principal is very crucial as a supervisor in implementing academic supervision. The implementation of academic supervision goes through the stages of planning, implementation, and evaluation or follow-up.